Six new species and a key to 12 species of the genus Diochus Erichson (Coleoptera: Staphylinidae, Staphylininae, Diochini) from India, Nepal and Pakistan - Huang, Tian; Janák, Jiří; Zhou, Hong-Zhang (Zootaxa, 2024)
This paper presents taxonomic studies of the genus Diochus Erichson, 1839 (Coleoptera: Staphylinidae, Staphylininae, Diochini) of Bhutan, India, Nepal, Myanmar, Pakistan and Thailand. Six new species are described: Diochus cameroni Huang, Janák & Zhou, sp. nov., D. emarginatus Huang, Janák & Zhou, sp. nov., D. setatus Huang, Janák & Zhou, sp. nov., D. setifer Huang, Janák & Zhou, sp. nov., D. keralanus Huang, Janák & Zhou, sp. nov. and D. ceylonicus Huang, Janák & Zhou, sp. nov. Six previously described species are revised here: D. guizhouensis Shuai, Nozaki & Tang, 2021 is recorded from India, Thailand and Myanmar for the first time; D. conicollis (Motschulsky, 1858) is recorded from Myanmar; and D. punctipennis (Motschulsky, 1858), D. ochraceus Cameron, 1926, D. antennatus (Motschulsky, 1858), D. bicoloripennis Coiffait, 1981 are redescribed based on the examination of type material. Lectotypes of Diochus major Kraatz, 1859 (synonym of D. conicollis (Motschulsky, 1858)), D. indicus Kraatz, 1859 (synonym of D. antennatus (Motschulsky) and Rhegmatocerus punctipennis Motschulsky, 1858 (valid name Diochus punctipennis (Motschulsky, 1858)) were designated. All species are illustrated and included in a key.